Education on the Use of Ginger Honey for Acute Respiratory Infections (ARI) - Dwi Okta Fuji Lestari; Azlina Fatika Dewi; Eka Efriani; Nova Hanipa; Endah Kusuma Pertiwi; Ema Yunita; Elfrida Turnip; Diyah Tepi Rahmawati (Universitas Dehasen Bengkulu, 2026)
Acute Respiratory Tract Infection (ARI) is an infectious disease that can affect the human respiratory system. ARI is an infection of the upper respiratory tract caused by microorganisms, including the nasal cavity, pharynx, and larynx, which lack gas exchange (Mustafa et al., 2023). An estimated 13 million people die from ARI. The disease burden varies widely, ranging from approximately 4 million of the 13 million people in India (48%), Indonesia (38%), Ethiopia (4.4%), Pakistan (4.3%), China (3.5%), Sudan (1.5%), and Nepal (0.3%). New ARIs occur in almost every region of the world. In 2022, Southeast Asia had the highest number of ARI cases worldwide. Approximately 30 countries contributed to the number of cases. (WHO, 2022) The incidence of ARI in Indonesia is relatively high, at 166,702 in 2022, reaching 53% of the 50% target. Of the 53% of ARI cases, 31.4% occurred in toddlers. ARI is the second leading cause of death in children under five (12-59 months), accounting for 9.4%. This disease is an acute respiratory infection with symptoms of fever, cough lasting less than two weeks, runny nose/nasal congestion, and/or sore throat (Ministry of Health of the Republic of Indonesia, 2022). In addition to medical treatment, ARI treatment can also be supported by the use of natural ingredients. The combination of ginger and honey has been shown to have a synergistic effect in relieving ARI symptoms. Ginger works to reduce inflammation and help expel mucus, while honey helps soothe irritated airway tissue, reduce coughing, and speed recovery. With the increasing number of ARI cases and the high public reliance on chemical medications, education on the use of ginger and honey is crucial as a safe, economical, and natural alternative that can be administered independently at home. Therefore, this educational activity is expected to increase public understanding of the use of herbal ingredients to support the treatment of mild ARI and encourage healthy lifestyles based on the use of local ingredients.